2010
DOI: 10.1310/tsr1704-318
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Kinesiotaping Combined With Botulinum Toxin to Reduce Plantar Flexors Spasticity After Stroke

Abstract: There is no clear benefit in adjuvant kinesiotaping application with botulinum toxin for correction of spastic equinus in stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1
14

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 12 publications
1
61
1
14
Order By: Relevance
“…This means that this increase in speed of 0.05 m/s is not an improvement that patients perceive as important. In addition, 2 studies found no significant improvement for the gait speed 24,29 , stressing that such results must still be better investigated. Finally, the methodological quality of the studies included in the meta-analysis is of low to moderate, which reinforces the caution in the interpretation of their results.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…This means that this increase in speed of 0.05 m/s is not an improvement that patients perceive as important. In addition, 2 studies found no significant improvement for the gait speed 24,29 , stressing that such results must still be better investigated. Finally, the methodological quality of the studies included in the meta-analysis is of low to moderate, which reinforces the caution in the interpretation of their results.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, 5 studies could not be included in metaanalysis 14,20,24,26,29 , and their results were only described in this review. Among these 5 studies, 3 reported that the gait speed has significantly improved 14,20,26 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations